Why Do Physicians Volunteer at Student-Run Free Clinics? A Look into What Drives or Hinders Their Participation - Greni, Susan; Radil, Stephanie; McIntire, Benjamin; Menning, Melanie (Journal of Student-Run Clinics, 2022)
Background: Student-run free clinics (SRFCs) provide students space to join and lead the care of patients who may not have access to care elsewhere. This is done under supervision of a physician preceptor who ensures safety and quality care while fostering a learning environment for students. The SRFC cannot function without physician preceptors. Concerns about retention and participation at the Student Health Alliance Reaching Indigent Needy Groups (SHARING) Clinic, a SRFC at University of Nebraska Medical Center (UNMC), fueled the investigation into motivations and barriers of physician volunteerism. This study aims to find why physicians volunteer and to propose meaningful strategies to increase retention rates at our institution and other SRFCs. Methods: An anonymous electronic survey was emailed to 348 physicians from various departments at UNMC. The survey assessed frequency of volunteerism, motivations and barriers, preceptor experiences, demographic information, and free form questions with respect to volunteering at the university associated SRFC. Results: Of the 348 survey recipients, 49 (13.5%) physicians responded. The most common barriers to physician volunteerism are work (n=23, 59%) and family obligations (n=23, 59%). The most common motivations are the ability to mentor students (n=14, 36%) and help patients in need (n=12, 31%). Of the respondents, 25 (61%) had never previously volunteered at SHARING. Of those who had volunteered, 7 (44%) reported volunteering at SHARING Clinic on average once or less per year over multiple years. Additionally, 13 (81%) volunteers report that they agree or strongly agree that they were satisfied with the experience and that it helped them improve their mentoring relationships with students. Conclusions: Collectively, the results indicate that the physicians sampled feel it is valuable to volunteer at the SRFC but are often impeded by other obligations. SRFCs may implement our proposed strategies to enhance motivations and mitigate barriers to physician volunteering.